Historical moments : changing interpretations of America's Past - McClellan, Jim R. (Guilford, Conn : Dushkin Pub. Group, 1994)
Contents: v.1. The pre-colonial period through the Civil War- - v.2. The Civil War through the 20th century.
Library has v. 2. only. Includes bibliographical references.
Keywords: United States -- History -- Sources; United States -- History